Design and Implementation of an Intelligent Cross-Border E-Commerce English Learning Platform Based on a Knowledge Map - Huang, Lei; Ma, Li (International Journal of Interactive Mobile Technologies (iJIM), 2024)
At present, most online education platforms still have problems such as single learning modes and loose knowledge structures. Using the knowledge map, the study employs a personalized adaptive intelligent adjustment strategy based on the structural expression of the CBEC English subject system. Firstly, the study uses the Scapy framework to crawl the subject knowledge data. Then use the LTP platform to process sentences containing multiple entities. Input the sentence into the dependency parser to analyze and extract the entity relationship. Finally, according to the relevance between knowledge points and topics in the knowledge map, the final learning path recommendation result is obtained. And cluster the similarity of curriculum content to build a complete curriculum system. Based on the above operations, a knowledge map-based smart learning platform for the CBEC English discipline has been designed and implemented to provide a smart, personalized learning environment for learners. According to the experimental analysis, the average satisfaction of learners with the learning platform designed by the study is 81.56%, which can meet the learning needs of learners and provide an excellent mobile learning environment for students.